Springer Science Reviews - Ozanne, Claire M. P.; Pappas, Maria L.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
No new submissions are being accepted because this journal ceases publication on December 31, 2017.
Keywords: Energy; Science; Medicine; Earth sciences; Life sciences; Environment; Life Sciences, general; Earth Sciences, general; Biomedicine, general; Environment, general; Energy, general; Science, Humanities and Social Sciences, multidisciplinary